2012
DOI: 10.1007/s10509-012-1152-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher-order corrections to ion acoustic waves in degenerate electron-positron-ion plasmas

Abstract: The nonlinear propagation of ion acoustic waves in ideal plasmas consisting of degenerate electrons and positrons, and isothermal ions is investigated. The Korteweg de Vries (K-dV) equation that contains the lowest order nonlinearity and dispersion is derived from the lowest order of perturbation and a linear inhomogeneous (K-dV type) equation that accounts for the higher order nonlinearity and the dispersion relation is obtained. The stationary wave solution for these equations has been found using the renorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…A few comments are in order, regarding the dispersion relation (24). First of all, we note that, taking into account (18), (24) takes the form…”
Section: Linear Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A few comments are in order, regarding the dispersion relation (24). First of all, we note that, taking into account (18), (24) takes the form…”
Section: Linear Analysismentioning
confidence: 99%
“…Recently, a lot of attention has been paid to the physics of electron-positron-ion quantum plasmas. In [23], the ionacoustic soliton formation in relativistic degenerate electronpositron-ion (e-p-i) plasma was investigated, with higher order nonlinear effects taken into account in [24]. A fully relativistic equation of state was assumed in [25].…”
Section: Introductionmentioning
confidence: 99%
“…A number of works (Hasan, 2016;Masood & Eliasso, 2011;Rahman et al, 2013;Hossen et al, 2014;Moghanjoughi, 2010; have been done by considering the degenerate electron-positron-ion plasma. Mehdipoor and Esfandyari-Kalejahi (Mehdipoor & Esfandyari-Kalejahi, 2012) studied the ion acoustic waves in a plasmas system consisting of degenerate electrons, positrons, and isothermal ions. They found that higher order corrections significantly change the properties of the Korteweg-de Vries solitons, and that under certain conditions, both compressive and rarefactive solitary waves exist in such a plasma system.…”
Section: Introductionmentioning
confidence: 99%
“…To remove discrepancies between experimentally observed characteristics/space data of solitary wave solitons and theoretical predictions, various studies [44][45][46][47][48][49] have proved the necessity of including higher-order nonlinearity and dispersion in studying nonlinear plasma waves. The new soliton solutions are called "dressed solitons."…”
Section: Introductionmentioning
confidence: 99%
“…Later, Akbari-Moghanjoughi [48] examined the possibility of propagation of bright-and dark-type solitary excitations by incorporating the higher-nonlinearity terms. Recently, Mehdipoor and Esfandyari-Kalejahi [49] proved that the higher-order corrections significantly change the properties of the KdV solitons propagating in an EPI plasma. However, all of these studies are only concerned with the electrostatic solitary wave solutions.…”
Section: Introductionmentioning
confidence: 99%